Liquid phase sintered aluminum alloys for binder jet printing
The combination of aluminum, silicon, and magnesium powders with controlled magnesium content in binder jet printing and liquid phase sintering addresses the densification challenges of aluminum powders by breaking oxide layers and forming nitride skeletons, achieving fully dense and accurate aluminum parts.
Patent Information
- Application Number
- CN202411253523.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-07
- Filing Date
- 2024-09-09
- Publication Date
- 2025-03-14
AI Technical Summary
Challenges in achieving complete densification of aluminum powders through traditional burnout processes due to their high reactivity and tendency to form stable oxide layers, which complicates the production of fully dense aluminum parts using additive manufacturing techniques like binder jetting.
A combination of aluminum, silicon, and magnesium powders, with magnesium content between 2.5 and 6.5 weight percent, is used for binder jet printing, followed by liquid phase sintering, where the mixture is carefully controlled for liquid phase fraction and temperature to break the oxide layer and form a nitride skeleton, enhancing densification and dimensional accuracy.
This approach enables the production of fully dense and dimensionally accurate aluminum parts by controlling the liquid phase sintering process, breaking the oxide layer, and forming a nitride skeleton, thus overcoming the limitations of traditional burnout processes.
Smart Images

Figure CN119609151A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to additive manufacturing. More specifically, the present disclosure relates to an aluminum alloy for additive manufacturing using binder jet printing. Background Art
[0002] The statements in this section merely provide background information related to the present disclosure and may not constitute prior art.
[0003] Binder jet printing is an effective additive manufacturing method for high-volume industrial production to fabricate net-shape metal structures with complex geometries and integrated functionality. Objects printed by this technology, i.e. green bodies, require a debinding and densification process to form a fully dense final part. In some applications, sintering is used for the densification of certain metal powders, which can produce uniform shrinkage and material bonds with desired strength. However, unlike other metal powders, aluminum powder is difficult to process to a fully dense state via sintering because the highly reactive surface conditions lead to the formation of a stable oxide layer.
[0004] Therefore, additional treatments or processes are typically used to achieve sintering of aluminum powder materials for additive manufacturing, which increases the manufacturing cycle time.
[0005] The present disclosure addresses these problems associated with binder jet printing of aluminum and aluminum alloy powders. Summary of the invention
[0006] This section provides a general summary of the disclosure and is not a comprehensive disclosure of its full scope or all of its features.
[0007] In one form of the present disclosure, an alloy includes a mixture of aluminum, tin, and magnesium. The amount of magnesium is between about 2.5% and 6.5% by weight of the mixture. The alloy is subjected to binder jet printing and liquid phase sintering.
[0008] In variations of this alloy that may be implemented individually or in any combination: the magnesium, the aluminum, and the tin are in the form of alloy powders; the magnesium, the aluminum, and the tin are mixed together to form a powder mixture; the magnesium, the aluminum, and the tin are combined in any combination of alloy and elemental powders; the amount of magnesium is between about 2.5% and 4% by weight of the mixture; the amount of tin is about 1% by weight of the mixture; full densification of the alloy is achieved for liquid fractions greater than about 8%; the liquid fraction is between about 8% and 20%; and the aluminum is an alloy of aluminum.
[0009] In another form of the present disclosure, a method of forming an alloy for binder jet printing includes mixing aluminum, tin, and magnesium to form a mixture. The amount of magnesium is between about 2.5% and 6.5% by weight of the mixture. The mixture is selectively combined with a binder to form a certain shape, the mixture is debonded, and the mixture is liquid phase sintered.
[0010] In a variation of the method that may be implemented individually or in any combination: the method further includes maintaining the mixture at about 500°C between debinding and liquid phase sintering; the magnesium, the aluminum and the tin are in the form of alloy powders; the magnesium, the aluminum and the tin are mixed together to form a powder mixture; the magnesium, the aluminum and the tin are combined in any combination of alloy and elemental powders; the amount of magnesium is between about 2.5 weight % and 4 weight % of the mixture; the amount of tin is about 1 weight % of the mixture; for a liquid phase fraction greater than about 8%, full densification of the alloy is achieved; and the aluminum powder is an alloy of aluminum.
[0011] In another form, the alloy comprises a mixture of aluminum, tin, and magnesium. The amount of tin is about 1 weight percent of the mixture, and the amount of magnesium is between about 2.5 weight percent and 6.5 weight percent of the mixture, and the remainder of the mixture is aluminum. The alloy is binder jet printed and liquid phase sintered.
[0012] In another variation of this alloy, the magnesium, the aluminum, and the tin are combined in any combination of alloys and elemental powders.
[0013] Further areas of applicability will become apparent from the description provided herein.It should be understood that the description and specific examples are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] In order that the present disclosure may be better understood, various forms of the present disclosure will now be described by way of example with reference to the accompanying drawings, in which:
[0015] Figure 1 shows experimentally measured density versus liquid fraction / sintering temperature curves for four powder materials according to the teachings of the present disclosure, which show that full density can only be achieved if >10% liquid fraction is produced during LPS;
[0016] Figure 2 According to the teachings of this disclosure, Figure 1 % tin powder and 4 wt % magnesium powder pre-alloyed side view, which shows that full density and acceptable dimensional accuracy are achieved for samples sintered at 10 to 20 liquidus fractions;
[0017] Figure 3 shows photographs and densities of final bodies sintered at about 20% liquid fraction according to the teachings of the present disclosure, showing that pre-alloying with 4 wt % Mg powder increases the final density of the three Al powder materials and improves dimensional accuracy;
[0018] Figure 4 shows experimentally measured density versus liquid fraction / sintering temperature curves for an Al-1 wt. % Sn system with various amounts of Mg in accordance with the teachings of the present disclosure, showing that the liquid fraction for reaching a plateau of a fully dense state increases with increasing amounts of Mg;
[0019] Figure 5 A photograph showing a representative microstructure of a liquid phase sintered sample according to the teachings of the present disclosure showing the formation of a skeleton structure when a holding stage is utilized;
[0020] Figure 6 shows a profile of a liquid phase sintered Al-5Mg-1Sn sample showing enhanced dimensional stability through the use of a holding stage in accordance with the teachings of the present disclosure; and
[0021] Figure 7 is a flow chart of a process for making an aluminum part according to the teachings of the present disclosure.
[0022] The drawings described herein are for illustration purposes only and are not intended to limit the scope of the present disclosure in any way. DETAILED DESCRIPTION
[0023] The following description is merely exemplary in nature and is not intended to limit the present disclosure, application, or uses. It should be understood that throughout the drawings, corresponding reference numerals indicate the same or corresponding parts and features.
[0024] In the sintering of aluminum alloys, the presence of magnesium is important for the cracking of the surface oxide formed on the aluminum powder. In addition, sintering at a temperature between the solidus temperature and the liquidus temperature (i.e., liquid phase sintering (LPS)) supports the densification process of the aluminum green body. However, the increase in the liquid phase volume reduces the dimensional accuracy of the parts. Therefore, the liquid phase fraction of the LPS of the aluminum powder material is well controlled within certain ranges to achieve densification while maintaining dimensional accuracy. At the same time, for the LPS of the aluminum powder material, it is also desired to form a nitride layer around the aluminum powder because the nitride layer can form a skeleton structure, which improves dimensional stability.
[0025] Based on the understanding of LPS as described above, the inventors have discovered several design factors for LPS of aluminum powder materials in order to enhance sintering of aluminum powder materials. First, magnesium is an important element because it can destroy the oxide layer; second, tin is present with aluminum powder, either as a separate powder or as an alloying element into the Al powder, because it can reduce the growth rate of the nitride layer; third, the nitrogen sintering atmosphere converts the oxide layer into the nitride layer; and further, the sintering temperature is selected to ensure that sintering occurs at a desired liquid phase fraction.
[0026] By including the described experimental factors, some aluminum powder materials (such as alloy 6061) can be sintered into final bodies with full density and reasonable dimensional accuracy. In previous studies, LPS of aluminum powder materials was found to be too fine to be compatible with large-scale industrial production because of the uneven temperature distribution and air flow that always exist in industrial sintering furnaces. This occurs when binder jet printing aluminum green bodies because the compaction step cannot be used to introduce plastic deformation to break the oxide layer or increase the contact area between particles to promote diffusion. In addition, binder jet printed objects have complex geometric features. Therefore, uniform shrinkage is desired to provide high dimensional stability during LPS.
[0027] According to the teachings of the present disclosure, a demonstrated method for enhancing the manufacturing robustness of LPS for binder jet printing of aluminum green bodies is provided. One form of the present disclosure provides three main components as described in detail below.
[0028] For the first component, the liquid phase fraction of the liquid phase sintered aluminum powder material is selected within 8% to 20% to provide an effective densification process and acceptable dimensional accuracy. For example, four commercially available aluminum powders including pure aluminum 201, 6061 and 7075 are mixed with 1 wt% tin powder and 4 wt% magnesium powder. As mentioned above, the addition of tin and magnesium is an important factor in achieving LPS of aluminum powder. The utilization of 4 wt% magnesium is discussed in detail below. After premixing, the powder material is then made into a cylindrical green body for subsequent sintering. The sintering process includes: a debonding stage for removing the binder, an intermediate holding stage for forming a rigid skeleton structure of the nitride (which will be discussed below in the third component), and a final sintering stage for densification. The sintering temperature of the final densification stage is selected to achieve different liquid fractions.
[0029] refer to Figure 1 , the final densities of the four powder materials were measured and plotted against the corresponding liquid fractions. Figure 1As shown by the dashed lines in , if about 8% liquid phase is generated during LPS, the full density of the four powder materials can be achieved. Specifically, if >10% liquid phase fraction is generated during LPS, the full density is achieved. However, once the liquid phase fraction is higher than 20%, the dimensional accuracy of the final body may be lost, as shown in FIG. Figure 2 shown. Specifically, Figure 2 Side views of some selected samples alloyed with 1 wt % tin powder and 4 wt % magnesium powder are shown, showing that samples sintered at liquidus fractions between 10% and 20% achieved full density and acceptable dimensional accuracy.
[0030] Acceptable dimensional accuracy of cylindrical shape and relatively smooth surface was achieved in all samples sintered with liquid fraction less than 20%. At higher liquid fractions, the samples had rough surfaces with pits. Therefore, selecting the liquid fraction of LPS of aluminum powder material within 10% to 20% resulted in an efficient densification process and acceptable dimensional accuracy.
[0031] For the second component, the present disclosure provides alloying with 2.5 wt % to 4 wt % of magnesium and alloying with tin to increase the final density and improve the dimensional accuracy of commercial aluminum powder materials. For example, three commercially available aluminum powder materials with different amounts of magnesium, including 201 (Al-Cu, 0.25 wt % Mg), 6061 (Al-Si-Mg, 1 wt % Mg) and 7075 (Al-Zn-Mg-Cu, 2.5 wt % Mg), are first mixed with 1 wt % of tin powder. The mixture of aluminum powder and tin powder is then made into a green body for subsequent sintering. (The sintering process is the same as previously described.) The sintering temperature of the final densification stage is selected to achieve a liquid fraction of less than 20% for different aluminum powder and tin powder combinations.
[0032] like Figure 3As shown, the density of the final body sintered at about 20% liquid fraction by alloying with additional 4 wt % Mg powder can increase the final density and improve the dimensional accuracy of aluminum powders 201, 6061 and 7075. Specifically, the final densities of 201+1 wt % Sn sintered at 610°C (24 vol % liquid), 6061+1 wt % Sn sintered at 630°C (21 vol % liquid), and 7075+1 wt % Sn sintered at 610°C (22 vol % liquid) are only 89.8%, 94.1%, and 94.1%, respectively, even though a liquid fraction of more than 20% has been achieved. In addition, the photos indicate that the final bodies of 201+1 wt % Sn and 6061+1 wt % Sn lose their cylindrical shape, while 7075+1 wt % Sn exhibits a cylindrical shape, but the top lip does not shrink as much as the rest of the segment. This indicates that increasing the total amount of magnesium above 2.5 wt% can improve both the final density and dimensional accuracy.Therefore, 4 wt% of magnesium powder was added to the mixture of aluminum powder material and tin powder material and made into the same cylindrical shape.
[0033] The green compacts were then sintered using the same three-stage sintering process but with different final sintering temperatures to produce a 20% liquid fraction, depending on the overall composition after alloying with 4 wt.% magnesium powder. (Results are in Figure 1 ) At the sintering temperature that forms a 20% liquidus fraction, the sample with 4 wt% magnesium can achieve a higher final density that is very close to a fully dense state and uniformly shrinks to maintain a cylindrical shape. In addition, increasing the total amount of magnesium will produce other benefits, including additional solid solution strengthening. However, this also shows that pre-alloying with magnesium powder needs to be maintained below a certain threshold, as determined by Figure 4 This is supported by the densification curve shown in . Specifically, Figure 4 Experimentally measured density versus liquid fraction / sintering temperature curves for the Al-1 wt% Sn system with various amounts of Mg are shown, showing that the liquid fraction for reaching a plateau of fully dense state increases with increasing Mg amount.
[0034] In addition, the final density of Al+1 wt% Sn powder materials with alloyed Mg between about 2.5 wt% and 6 wt% was measured at different final sintering temperatures, and Figure 4. Therefore, the liquid phase fraction for achieving a fully dense state increases with the increase in the amount of magnesium. Therefore, when the amount of magnesium is higher than 5% by weight, the liquid phase fraction for achieving a fully dense state exceeds 20%, and the dimensional accuracy is reduced at this time. Therefore, the alloying of magnesium between about 2.5% by weight and 6% by weight can enhance the sintering performance of commercial aluminum powder materials in terms of final density and dimensional stability. In some variations, the amount of Mg is between about 2.5% by weight and 6.5% by weight of the mixture. In some variations, one or more of aluminum, tin and magnesium is in powder form as an element powder, that is, a powder form of a single element. In other variations, one or more of aluminum, tin and magnesium are each in powder form as an alloy powder, that is, aluminum, tin and / or magnesium alloy powders may include other components. In other variations, aluminum, tin and magnesium are combined together into a powder mixture of elements or as an alloy powder that may include other components.
[0035] It should also be understood that the element ranges discussed herein include all incremental values between the minimum element composition value and the maximum element composition value. That is, the range of the minimum element composition value can be from the minimum value to the maximum value. Similarly, the range of the maximum element composition value can be from the maximum value shown to the minimum value discussed. For example, the minimum Mg content can be 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.1, 3.2, 3.3, 3.4, 3.5, 3.6, 3.7, 3.8, 3.9, 4.0, 4.1, 4.2, 4.3, 4.4, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.1, 5.2, 5.3, 5.4, 5.5, 5.6, 5.7, 5.8, 5.9, 6.0, 6.1, 6.2, 6.3, 6.4, 6.5 and any value between these incremental values. , and the maximum Mg content can be 6.5, 6.4, 6.3, 6.2, 6.1, 6.0, 5.9, 5.8, 5.7, 5.6, 5.5, 5.4, 5.3, 5.2, 5.1, 5.0, 4.9, 4.8, 4.7, 4.6, 4.5, 4.4, 4.3, 4.2, 4.1, 4.0, 3.9, 3.8, 3.7, 3.6, 3.5, 3.4, 3.3, 3.2, 3.1, 3.0, 2.9, 2.8, 2.7, 2.6, 2.5 and any value between these incremental values.
[0036] For the third component, the present disclosure provides that an intermediate holding stage between the debonding stage and the final sintering stage can promote the formation of a rigid nitride skeleton structure, which enhances the dimensional stability of the aluminum powder material. For example, two aluminum powder materials, Al-4Mg-1Sn and 6061-4Mg-1Sn, were sintered with two different thermal cycles. The first method utilized a two-stage sintering consisting only of a debonding stage and a sintering stage, while the second method included an additional intermediate holding stage at 500°C for 60 minutes. Figure 5 The significant differences in LPS microstructures of both Al-4Mg-1Sn powder material and 6061-4Mg-1Sn powder material with and without an intermediate holding stage are shown. Specifically, Figure 5 A representative microstructure of a liquid phase sintered sample is shown, illustrating the skeletal structure formed with the use of an intermediate holding stage.
[0037] exist Figure 5 (a) and Figure 5 The sample with the intermediate holding stage shown in (c) shows nitride structures around the previous Al grains. Energy dispersive spectroscopy analysis confirmed that these were nitride phases. Removal of the intermediate holding stage resulted in larger Al grains and fewer nitride structures, as shown in Figure 2. Figure 5 (b) and Figure 5 (d). It should be noted that Figure 3 The very dark phase shown in Figure 1 was identified as the Mg2Sn phase. Therefore, the experimental results indicate that the 3-step thermal cycle including an intermediate holding stage promotes the formation of a nitride skeleton structure for the aluminum powder material. To further elucidate the benefit of the nitride skeleton structure, the profile of the sample after LPS was recorded using a stereo microscope.
[0038] Figure 6 Representative photographs of Al-5Mg-1Sn samples are shown in , which show representative photographs of the outlines of liquid-phase sintered Al-5Mg-1Sn samples, indicating the enhanced dimensional stability by the intermediate holding stage.
[0039] Green parts and associated stereomicroscope recorded profiles, such as Figure 6 (a) and Figure 6 (b) show cylinders with sharp parallel edges. If the liquid fraction in the final sintering stage is lower than 15%, the sintered samples show uniform shrinkage regardless of whether an intermediate holding stage is used, as shown in Figure 6 (c) and Figure 6 However, when the liquid phase is between 15% and 20%, the samples without the intermediate holding stage do not form or form less nitride skeleton structure, so that the cylinder after LPS is not maintained, as shown in FIG. Figure 6On the other hand, for the samples with an intermediate holding stage, uniform shrinkage is still observed even when a liquid fraction of >15% is formed during the LPS, as shown in (f). Figure 6 (e). Thus, the enhanced dimensional stability is a result of the nitride skeleton structure promoted by the intermediate holding stage. In other words, 3-stage sintering with a dedicated intermediate holding stage provides dimensional stability but also allows densification, as well as allowing a wider sintering window.
[0040] refer to Figure 7 , a process 100 is shown, which summarizes the above steps of forming a liquid phase sintered alloy for binder jet printing. In step 102, a sintering temperature is selected to achieve densification while maintaining dimensional accuracy. In step 104, aluminum powder, tin powder, and magnesium powder are mixed together to form a mixture within a specified composition range to increase the strength of the sintered body, extend the LPS execution conditions, and promote the formation of a nitride layer. In step 106, the mixture is mixed with a binder to form a certain shape. In step 108, the mixture is debonded. In step 110, a holding stage is used between the debonding stage and the sintering stage to further promote the formation of the nitride layer into a rigid skeleton structure. And in step 112, the mixture is liquid-phase sintered with a nitrogen atmosphere, which converts the oxide layer into a nitride layer at a sintering temperature, and the sintering temperature is selected to ensure that sintering occurs with a desired liquid phase fraction.
[0041] Unless otherwise expressly indicated herein, all numerical values indicating mechanical / thermal properties, composition percentages, dimensions and / or tolerances or other characteristics when describing the scope of the present disclosure should be understood to be modified by the word "about" or "approximately". Such modifications are desirable for a variety of reasons, including: industrial practice; material, manufacturing and assembly tolerances; and testing capabilities.
[0042] As used herein, the phrase at least one of A, B, and C should be construed to mean a logical (A or B or C), using a non-exclusive logical "or", and should not be construed to mean "at least one of A, at least one of B, and at least one of C."
[0043] The description of the present disclosure is merely exemplary in nature, and thus, variations that do not depart from the essence of the present disclosure are intended to be within the scope of the present disclosure. Such variations should not be regarded as a departure from the spirit and scope of the present disclosure.
[0044] According to the present invention, there is provided an alloy for liquid phase sintering in binder jet printing having: a mixture of: aluminum; tin; and magnesium, wherein the amount of magnesium is between about 2.5 wt % and 6.5 wt % of the mixture.
[0045] According to an embodiment, the magnesium, the aluminum and the tin are in the form of alloy powder.
[0046] According to an embodiment, the magnesium, the aluminum and the tin are mixed together to form a powder mixture.
[0047] According to an embodiment, the magnesium, the aluminum, and the tin are combined in any combination of alloys and elemental powders.
[0048] According to an embodiment, the amount of magnesium is between about 2.5% and 4% by weight of the mixture.
[0049] According to an embodiment, the amount of tin is about 1 wt % of the mixture.
[0050] According to an embodiment, full densification of the alloy is achieved for liquid fractions greater than about 8%.
[0051] According to an embodiment, the liquid phase fraction is between about 8% and 20%.
[0052] According to an embodiment, the aluminum is an alloy of aluminum.
[0053] According to the present invention, a method of forming an alloy for binder jet printing includes: mixing: aluminum; tin; and magnesium to form a mixture, wherein the amount of magnesium is between about 2.5 weight % and 6.5 weight % of the mixture; selectively combining the mixture with a binder to form a certain shape; debinding the mixture; and liquid phase sintering the mixture with nitrogen.
[0054] In one aspect of the invention, the method includes maintaining the mixture at about 500° C. between debinding and liquid phase sintering.
[0055] In one aspect of the present invention, the magnesium, the aluminum and the tin are in the form of alloy powder.
[0056] In one aspect of the invention, the magnesium, the aluminum and the tin are mixed together to form a powder mixture.
[0057] In one aspect of the invention, the magnesium, the aluminum, and the tin are combined in any combination of alloys and elemental powders.
[0058] In one aspect of the invention, the amount of magnesium is between about 2.5% and 4% by weight of the mixture.
[0059] In one aspect of the invention, the amount of tin is about 1% by weight of the mixture.
[0060] In one aspect of the invention, full densification of the alloy is achieved for liquid fractions greater than about 8%.
[0061] In one aspect of the present invention, the aluminum powder is an alloy of aluminum.
[0062] According to the present invention, there is provided an alloy for liquid phase sintering in binder jet printing, having: a mixture of: aluminum; tin; and magnesium, wherein the amount of tin is about 1 weight percent of the mixture, and the amount of magnesium is between 2.5 weight percent and 6.5 weight percent of the mixture, and wherein the remainder of the mixture is aluminum.
[0063] According to an embodiment, the magnesium, the aluminum, and the tin are combined in any combination of alloys and elemental powders.
Claims
1. An alloy for liquid phase sintering in binder jet printing, the alloy comprising: A mixture of: aluminum; tin; as well as magnesium, The amount of magnesium is between about 2.5% and 6.5% by weight of the mixture.
2. The alloy of claim 1, wherein the magnesium, the aluminum and the tin are in the form of alloy powder.
3. The alloy of claim 1, wherein the magnesium, the aluminum, and the tin are mixed together to form a powder mixture.
4. The alloy of claim 1 wherein said magnesium, said aluminum and said tin are combined in any combination of alloys and elemental powders.
5. The alloy of claim 1, wherein the amount of magnesium is between about 2.5% and 4% by weight of the mixture.
6. The alloy of claim 1, wherein the amount of tin is about 1% by weight of the mixture.
7. The alloy of claims 1 to 6, wherein full densification of the alloy is achieved for liquid fractions greater than about 8%.
8. The alloy of claim 7, wherein the liquidus fraction is between about 8% and 20%.
9. The alloy of claim 1, wherein the aluminum is an alloy of aluminum.
10. A method of forming an alloy for binder jet printing, the method comprising: mix: aluminum; tin; as well as magnesium to form a mixture, wherein the amount of magnesium is between about 2.5% and 6.5% by weight of the mixture; selectively combining the mixture with a binder to form a shape; Debonding the mixture; as well as The mixture was liquid phase sintered using nitrogen.
11. The method of claim 10, further comprising maintaining the mixture at about 500°C between debinding and liquid phase sintering.
12. The method of claim 10, wherein the magnesium, the aluminum, and the tin are in the form of an alloy powder.
13. The method of claim 10, wherein the magnesium, the aluminum, and the tin are mixed together to form a powder mixture.
14. The method of claim 10, wherein the magnesium, the aluminum, and the tin are combined in any combination of alloys and elemental powders.
15. The method of claim 10, wherein the amount of tin is about 1% by weight of the mixture.